Studi Historis dan Kodikologis Manuskrip dan Terjemahan Al-Qur’an Abad XIII-XX di Tiongkok: Historical and Codicological Study of Koran Manuscripts and Translations in the 13th-20th Centuries in China - Adib Afhan (Besari: Journal of Social and Cultural Studies, 2025)
This study examines the development of Islam in China through the history of translation and the analysis of Koran manuscripts from codicological and cultural perspectives. Using a descriptive, library-based research method with content analysis, data were drawn from Islamic history literature, translation history, and Koran codicological studies. The findings indicate that the translation of the Koran into Chinese was significantly delayed due to the intellectual isolation of Chinese Muslims, the dominance of Arabic as a sacred language, and linguistic and cultural differences between Arabic and Chinese. Furthermore, Koran manuscripts produced in China between the 13th and 14th centuries exhibit stylistic and structural influences from Central Asian manuscript traditions, transmitted through Muslim migrant communities, both orally and in manuscript copies. This study enriches Koranic studies and Islamic historiography in East Asia by highlighting the dynamic interaction between Islamic sacred texts and local cultural traditions.  Studi ini meneliti perkembangan Islam di Tiongkok melalui sejarah penerjemahan dan analisis manuskrip Al-Quran dari perspektif kodikologi dan budaya. Dengan menggunakan metode penelitian deskriptif berbasis pustaka dengan analisis isi, data diambil dari literatur sejarah Islam, sejarah penerjemahan, dan studi kodikologi AlQuran. Temuan menunjukkan bahwa penerjemahan Al-Quran ke dalam bahasa Tionghoa sangat tertunda karena isolasi intelektual Muslim Tiongkok, dominasi bahasa Arab sebagai bahasa suci, dan perbedaan linguistik dan budaya antara bahasa Arab dan Tionghoa. Lebih lanjut, manuskrip Al-Quran yang diproduksi di Tiongkok antara abad ke-13 dan ke-14 menunjukkan pengaruh gaya dan struktur dari tradisi manuskrip Asia Tengah, yang ditransmisikan melalui komunitas migran Muslim di sepanjang Jalur Sutra, baik secara lisan maupun dalam bentuk manuskrip. Studi ini memperkaya studi Al-Quran dan historiografi Islam di Asia Timur dengan menyoroti interaksi dinamis antara teks-teks suci Islam dan tradisi budaya lokal.